The Effect of Family Interaction and Decision-Making Toward Marital Quality of Family with Migrant Husband - Tin Herawati; Inne Nurajizah (Journal of Family Sciences, 2016)
Lagging economic conditions, especially in rural areas cause residents leave their hometown or become a migrant to get a job in order to meet the family needs. This study aimed to analyze the influence of family characteristics, family interaction, and decision-making on marital quality in families with migrant husband. The design of this study was cross sectional study involving wives, who had migrant husbands and teenage children (age 12-18), as respondents. The study was conducted in Banyuresmi Village, Garut Regency, West Java, Indonesia which were selected purposively. Data were collected through interview using questionnaire. The results showed that family income and conjugal interaction were the factors that allowed an increase in marital quality. On the other hand, decision-making did not have a significant effect on marital quality of the family with migrant husband